Amor, nación e identidad en Rodil: del teatro de Ricardo Palma al de Sebastián Salazar Bondy - Santistevan de Noriega, Luis Alfonso (2024)
This paper comparatively analyzes the works entitled Rodil written one hundred years apart by Ricardo Palma (1851) and Sebastián Salazar Bondy (1951) inspired by the same historical event: the resistance of the Spanish brigadier Rodil in the Real Felipe del Callao after the royalist capitulation. Taking into account the different contexts, the similarities and divergences of the works  are sought in the treatment of discourses on power, social classes, generations, ideologies, the body, independence, women and heterosexual love. Special attention is paid to the allegorization of the nation in women and what the plays propose as a denouement to represent a foundational moment of national identity.